(untitled) (Iranian Journal of Kidney Diseases, 2013)
Introduction. Low fetuin-A and vitamin D and high monounsaturated fatty acid (MUFA) contents are associated with vascular calcification (VC) in dialysis patients. We aimed to demonstrate the difference in fetuin-A, vitamin D, MUFA, and VC on plain radiography between patients on hemodialysis and peritoneal dialysis (PD). Materials and Methods. We recruited 31 hemodialysis and 30 PD patients. We examined plain radiography of the feet, hands, pelvis, and lateral lumbar spine and defined significant VC as abdominal aortic calcifications scores of 5 and higher, VC scores of the hands and pelvis of 3 and higher, or arterial media calcifications of the feet on plain radiography. Results. The mean age, dialysis duration, and prevalence of VC on plain radiography were not significantly different in PD patients compared to hemodialysis patients. However, fetuin-A (P < .001) and MUFA (P = .001) were significantly higher, whereas serum albumin and 25-hydroxyvitamin D (P < .001) were significantly lower in PD patients compared to hemodialysis patients. Hemodialysis patients who demonstrated significant VC on plain radiography had longer dialysis vintage, higher prevalence of coronary artery disease, and higher MUFA than patients without significant VC. Peritoneal dialysis patients who demonstrated significant VC on plain radiography had lower fetuin-A levels and higher C-reactive protein than patients without significant VC. Fetuin-A was an independent risk factor related with VC on plain radiography in PD patients. Conclusions. Fetuin-A, 25-hydroxyvitamin D, and MUFA were significantly different, although the prevalence of VC on plain radiography was not different according to dialysis modality.